Exploring the Dichotomy Between Training Versus Inner Training in Ogun State Correctional Facilities Among the Recidivists in Nigeria - OGUNMEFUN, Folorunsho Muyideen; OGUNNOWO, Ruth Ooreofe; ADEFUYE, Jesudamiloju Esther (Integration: Journal Of Social Sciences And Culture, 2025)
Purpose:The importance of quality training in any organization cannot be underrated in the procedure of reintegration of ex-offenders back into the larger society for the maintenance of social orderliness in Nigeria. Failure to capture the problem of inner training from role models with recidivists had degenerated into an ever-increasing nature of ex-offenders released from prison returning to the prisons for either the same problem or an advanced problem.Methodology:Social learning theory by Bandura was adopted. A qualitative method was adopted with a non-experimental research design with a purposive sampling technique. Fifteen recidivists were selected from four (4) correctional facilities in Ogun State, Nigeria Semi-structured questionnaire was designed and used as a guide to conduct in-depth interviews among the selected recidivists. However, after screening, coding and editing, thirteen (13) recidivists' interviews were found useful for the content systematic method of data analysis and interpretation.Findings:The study concluded that inner training shared among recidivists contributes largely to the rate at which ex-offenders return to prisons for several reasons.Implication:Therefore, the following recommendations were stated: the creation of a post-released services scheme, the Creation of quality aftercare monitoring, and the Development of an alternative to imprisonment between new inmates and ex-offenders in the prisons.